2021
DOI: 10.1038/s41598-020-79184-3
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle disease virus transmission dynamics in wild peridomestic birds in the United Arab Emirates

Abstract: To understand the dynamics of a pathogen in an animal population, one must assess how the infection status of individuals changes over time. With wild animals, this can be very challenging because individuals can be difficult to trap and sample, even more so since they are tested with imperfect diagnostic techniques. Multi-event capture-recapture models allow analysing longitudinal capture data of individuals whose infection status is assessed using imperfect tests. In this study, we used a two-year dataset fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Hoye et al, (2010) showed that AIV-H5 could be transmitted between domestic poultry and wild birds, especially for H5 subtype. Newcastle disease virus is one of the most impor-tant viral diseases in domestic birds as well as wild birds (Snoeck et al, 2013;Hirschinger et al, 2021). Even though hundreds of reports about AIV-H5 and NDV surveillance in wild birds are available but there is limited or no information of AIV-H5 in swiflet bird.…”
Section: Discussionmentioning
confidence: 99%
“…Hoye et al, (2010) showed that AIV-H5 could be transmitted between domestic poultry and wild birds, especially for H5 subtype. Newcastle disease virus is one of the most impor-tant viral diseases in domestic birds as well as wild birds (Snoeck et al, 2013;Hirschinger et al, 2021). Even though hundreds of reports about AIV-H5 and NDV surveillance in wild birds are available but there is limited or no information of AIV-H5 in swiflet bird.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on the effect of wild bird droppings as a source of Campylobacter jejuni in children's playgrounds showed that the presence of wild birds, including Laughing Doves, can cause acute gastroenteritis in humans, especially in children (Abdollahpour et al, 2015). In addition, Laughing Doves can cause damage by transmitting the Newcastle disease virus (NDV) to the poultry industry (Okpanachi et al, 2020;Hirschinger et al, 2021). Therefore, with a better understanding of the characteristics of Laughing Dove nest sites, if necessary, we can take steps to make some places unsuitable for nesting this species and avoid possible damages.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SCR models are also being used to estimate population processes such as within group dispersal and survival through the use of spatial multi-event capture recapture models (Weiser et al 2018). Multi event capture recapture models not only estimate population densities but also allow for the estimation of transitions between states; for example survival or seroconversion (Sapsford et al 2015; Hirschinger et al 2021), allowing users to better understand the role of various aspects of behaviour in state transmission dynamics. This may provide insights into the mechanisms underpinning key processes such as survival and disease transmission.…”
Section: Introductionmentioning
confidence: 99%